Associations between adolescents' preference for fitness activities and achieving the recommended weekly level of physical activity - Michal Kudlacek; Karel Fromel; Dorota Groffik (Elsevier, 2020)
Background/Objective: This study aimed to explore differences in rates of achieving the weekly physical activity (PA) recommendation between adolescents who preferred fitness PA and those who did not. Furthermore, we investigated the types of PA practiced by adolescents. Methods: In total, 9513 participants from the Czech Republic and Poland, aged 15-18 years took part in the study between 2009 and 2016. Out of this source sample, 4977 self-reported their weekly PA using the IPAQ-Long Form, and 1348 objectively monitored their weekly PA using pedometers and recorded the type of PA. Results: Boys ranked fitness PA third, after team and individual sports. For girls, the preference for fitness PA grew at the expense of dance and outdoor PA. Among Czech and Polish boys as well as Czech girls, those who preferred fitness PA were more likely to achieve the recommended weekly PA level than those who did not prefer fitness PA. We did not find a significant difference in other types of PA and rates of achieving the recommendation of 11,000 steps/day. Preference for fitness PA was associated with an increased likelihood (OR = 1.30; 95% CI = 1.12-1.52; p < 0.001) of achieving the recommendation for PA. Conclusions: When promoting adolescents' PA, it is necessary to consider preferred PA types. The PA recommendation was met by almost 33% of adolescents who indicated a preference for fitness PA, but only by 22% of those not preferring fitness activities. Organized PA is also important for meeting PA recommendations. Keywords: IPAQ-Long, Preferences, Recommendation, Step count, Pedometer, Monitoring